Hematologic changes in propofol-anesthetized dogs with or without tramadol administration - Costa, P. F. [UNESP]; Nunes, N. [UNESP]; Belmonte, E. A. [UNESP]; Moro, J. V. [UNESP]; Lopes, P. C. F. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2013)
Drugs commonly used in anesthesia practice may significantly alter the oxidative state of blood cells. This mechanism could contribute to the immune suppression that occurs transiently in the early postoperative period. Thus, we assessed the effects of continuous rate infusion (CRI) of propofol associated or not with tramadol on hematologic parameters in dogs. Eight adult mongrel dogs were anesthetized on 2 occasions, 15 d apart. Two groups were formed: control group (CG) and tramadol group (GT). Propofol was used for induction (10mg kg-1) followed by a CRI (0.7mg kg-1minute-1). The animals were positioned in lateral recumbency and mechanically ventilated with inspired oxygen fraction of 0.6. In TG, tramadol (2mg kg-1) followed by a CRI (0.5mg kg-1minute-1) was administered in dogs. In the CG the sodium chloride (NaCl) solution at 0.9% was administered followed by its CRI, in the same volume that was used in TG. The measurement was taken before anesthesia induction (Tbasal), 30 minutes after induction (T0) and then at 30-minute intervals (T30 to T60). Red blood cells, hematocrit, hemoblogin concentration and total leukocytes count decreased from T0 in both groups. In TG, lymphocytes count at Tbasal [1.86 (0.82) x103µl-1] was greater than at T0, T30 and T60 [0.96(0.50), 0.92(0.48) and 0.95(0.48) x103µl-1, respectively]. No significant differences were observed for platelets neutrophil, eosinophil, basophil and monocyte count. In dogs, propofol-anesthesia associated or not with tramadol promoted decrease in blood cell count and should be used with caution in immunossupressed patients.

Fármacos comumente utilizados na prática anestésica podem alterar significativamente o estado oxidativo das células sanguíneas. Esse mecanismo pode contribuir para a supressão imunológica que ocorre transitoriamente no pós-operatório imediato. Assim, foram avaliados os efeitos da infusão contínua (CRI) de propofol associado ou não com tramadol sobre parâmetros hematológicos em cães. Oito cães adultos foram anestesiados em duas ocasiões, com 15 dias de intervalo. Dois grupos foram formados: grupo-controle (CG) e grupo tramadol (TG). O propofol foi utilizada para a indução (10mg kg-1), seguido por CRI (0,7mg kg-1 minuto-1). Os animais foram posicionados em decúbito lateral e ventilados com fração inspirada de oxigênio de 0,6. Em TG, tramadol (2mg kg-1), seguido por CRI (0,5kg de 1 minuto-1mg), foi administrado em cães. Enquanto no CG, o cloreto de sódio solução (NaCl) a 0,9% foi administrado seguido por sua CRI, no mesmo volume que foi usado no TG. As mensurações das variáveis foram realizadas antes da indução anestésica (Tbasal), 30 minutos após a indução (T0) e em intervalos de 30 minutos (T30 a T60). Hemácias, hematócrito, hemoglobina e leucócitos totais diminuíram a partir de T0 em ambos os grupos. No TG, contagem de linfócitos no Tbasal [1,86 (0,82) x103µl-1] foi maior do que em T0, T30 e T60 [0,96 (0,50), 0,92 (0,48) e 0,95 (0,48) x103µl-1, respectivamente]. Não foram observadas diferenças significativas para plaquetas, neutrófilos, eosinófilos, basófilos e monócitos. Em cães, anestesia com propofol associado ou não ao tramadol promove alterações importantes no hemograma e deve ser utilizada com cautela em pacientes imunossuprimidos.
Alterações hematológicas em cães anestesiados com infusão contínua de propofol, associado ou não ao tramadol
Keywords: Anestesia total intravenosa; Células sanguíneas; Hematologia; Opioide; Blood cells; Hematology; Opioid; Total intravenous anesthesia